STATUS GIZI ANAK DENGAN PEMBERIAN ASI DAN MP-ASI DIBANDINGKAN DENGAN PEMBERIAN SUSU FORMULA DAN MP-ASI PADA USIA 6-12 BULAN - Hanif Habibur Rohman (FKU 16 UMY 043, 2016)
Malnutrition in Indonesia is still quite high. South East Asia Nutrition Survey (Seanuts) conducted by Frisian Campina and Nutrition Experts Association of Indonesia said that the Indonesian children aged 6-12 years a lack of protein up to 80 percent of adequacy rate which has been determined by the World Health Organization in Indonesia. At ranging in age from 6 months MP-ASI also be given so that the nutritional needs can be met. Objective : This study was to determine the nutritional status of children with breastfeeding and breast milk compared with formula feeding and complementary feeding at age 6-12 months Methods : This study is observational analytic cross sectional method, sampling in this study using a non-probability sampling technique (non-random) sampling is not random. The technique used is purposive sampling with inclusion criteria. The data obtained are then processed by Chi-Square Tests. Results : The results of the study sample size in this study was 75, divided into two groups: children with breastfeeding and complementary feeding and child with formula feeding and breast milk. Asymp value. Sig. obtained amounted to 0,113, for a value Asymp. Sig. 0.113> 0.05 then the corresponding basis for decision making in the Chi-Square Tests can be concluded H0. Rejection H0 containing that no significant difference in a child with breastfeeding and breast milk compared with formula feeding and complementary feeding at age 6-12 months. Conclusion : There is no significant difference in nutritional status in children with breastfeeding and breast milk compared with formula feeding children and breast milk. Keywords : Nutritional status, breast milk and breast milk, infant formula and breast milk, Children Ages 6-12 months.